Hsp90 breaks the deadlock of the Hsp70 chaperone system - Morán Luengo, Tania; Kityk, Roman; Mayer, Matthias P.; Rüdiger, Stefan G.D. (Molecular cell, 2018)
Summary - Protein folding in the cell requires ATP-driven chaperone machines such as the conserved Hsp70 and Hsp90. It is enigmatic how these machines fold proteins. Here, we show that Hsp90 takes a key role in protein folding by breaking an Hsp70-inflicted folding block, empowering protein clients to fold on their own. At physiological concentrations, Hsp70 stalls productive folding by binding hydrophobic, core-forming segments. Hsp90 breaks this deadlock and restarts folding. Remarkably, neither Hsp70 nor Hsp90 alters the folding rate despite ensuring high folding yields. In fact, ATP-dependent chaperoning is restricted to the early folding phase. Thus, the Hsp70-Hsp90 cascade does not fold proteins, but instead prepares them for spontaneous, productive folding. This stop-start mechanism is conserved from bacteria to man, assigning also a general function to bacterial Hsp90, HtpG. We speculate that the decreasing hydrophobicity along the Hsp70-Hsp90 cascade may be crucial for enabling spontaneous folding.
Published: April 26, 2018
Gesehen am 22.07.2019